2019
DOI: 10.24251/hicss.2019.017
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Network Visualization for Innovation and Competitive Intelligence

Abstract: Technology positions of a firm may determine its competitive advantages and innovation opportunities. While a tangible understanding of the technology positions of a firm, i.e., the set of technologies the firm has mastered, can inform innovation and competitive intelligence, yet such positions are heterogeneous, intangible and difficult to analyze. Herein, we present a data-driven network visualization methodology to locate the knowledge positions of a firm as a subspace of the total technology space for inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Organisasi yang sukses menggunakan pengetahuan teknologi dan pasar untuk mendapatkan keuntungan (Rakthin et al, 2016). Karena posisi teknologi suatu organisasi dapat ditentukan oleh keunggulan kompetitif dan peluang inovasinya, rangkaian teknologi yang akan dikuasai organisasi mencakup inovasi dan kinerja CI (Sarica et al, 2019). Penelitian Bisson &;Tang Tong (2018) memberikan bukti empiris untuk mempromosikan pelatihan dan adopsi teknologi di antara perusahaan untuk mencapai praktik CI yang lebih tinggi.…”
Section: Faktor Pasarunclassified
“…Organisasi yang sukses menggunakan pengetahuan teknologi dan pasar untuk mendapatkan keuntungan (Rakthin et al, 2016). Karena posisi teknologi suatu organisasi dapat ditentukan oleh keunggulan kompetitif dan peluang inovasinya, rangkaian teknologi yang akan dikuasai organisasi mencakup inovasi dan kinerja CI (Sarica et al, 2019). Penelitian Bisson &;Tang Tong (2018) memberikan bukti empiris untuk mempromosikan pelatihan dan adopsi teknologi di antara perusahaan untuk mencapai praktik CI yang lebih tinggi.…”
Section: Faktor Pasarunclassified
“…These valuables techniques help us better understand the nature of the knowledge search practices used by inventors to design new inventions and their occurrence in the global technological landscape. Furthermore, still based on patent analytics, scholars have also developed more applied research conducting analyses at firm level, in order to help a given firm identify what new knowledge components could be combined with their established knowledge to design new inventions (e.g., Nakamura et al, 2015;Sarica et al, 2019). Thus, the design of new inventions is closely related to a firm's knowledge base, whose structure matters in this regard.…”
Section: Knowledge Search Practices: (Re)combination and The Design Of New Inventionsmentioning
confidence: 99%
“…It is therefore essential to link technology intelligence to CI in sustaining competitiveness. This result shows that the technology position of an organisation determines its competitive advantage, innovation opportunities, and CI (Sarica et al, 2019).…”
Section: Technologymentioning
confidence: 80%
“…Similarly, Koriyow and Karugu (2018) found that CI assisted in monitoring technology, customer base, competitors, ecology, suppliers and economics. This result implies that an organisation's technology position may determine its competitive advantage and innovation opportunities, so the set of technologies the organisation has mastered informs innovation and CI (Sarica et al, 2019). Tahmasebifard and Wright (2018) opined that technical information about competitors could impact a company's competitive advantage.…”
Section: Technologymentioning
confidence: 99%